ijsr 2020
DOI: 10.36106/ijsr/8116404
|View full text |Cite
|
Sign up to set email alerts
|

Needle-Stick and Sharp Injuries (Nsis) Among Health Care Workers: A Cross Sectional Study in a Tertiary Health Care Institution Of Kolkata, India

Abstract: Background: NSI is an important but preventable occupational hazard among Health care workers (HCWs) all over the world. Objective:To assess prevalence of NSIs and related knowledge and practices among HCWs of a tertiary health care institution. Methods: It was an institution based, cross sectional study done among junior doctors (interns and house staffs) and nurses in a tertiary health care institution of Kolkata. Complete enumeration was done and sample size was 215. Aself-administered questionnaire was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…According to the 2007 Physicians Health Study, 40% of the 19000 doctors were overweight and 23% were obese [12]. While a study from Kolkata done by Das et al reported 81.9% of the medical professionals were overweight or obese (73.5% obese) [13]. Burden of obesity in medical professional was around 50-70% in the previous studies in India [2,14].…”
Section: Discussionmentioning
confidence: 99%
“…According to the 2007 Physicians Health Study, 40% of the 19000 doctors were overweight and 23% were obese [12]. While a study from Kolkata done by Das et al reported 81.9% of the medical professionals were overweight or obese (73.5% obese) [13]. Burden of obesity in medical professional was around 50-70% in the previous studies in India [2,14].…”
Section: Discussionmentioning
confidence: 99%